IL-17 Affects the Progression, Metastasis, and Recurrence of Laryngeal Cancer via the Inhibition of Apoptosis through Activation of the PI3K/AKT/FAS/FASL Pathways - Yang Song; Ming Yang; Hongjian Zhang; Yan Sun; Ye Tao; Huihui Li; Jing Zhang; Yuncheng Li; Jianming Yang (Journal of Immunology Research)
Background. Cytokines play important roles in the development and prognosis of laryngeal cancer (LC). Interleukin-17 (IL-17) from a distinct subset of CD4+ T cells may significantly induce cancer-elicited inflammation to prevent tumor immune surveillance. Methods. The expression levels of IL-17 were examined among 60 patients with LC. Immunofluorescence colocalization experiments were performed to verify the localization of IL-17 and FAS/FASL in Hep-2 and Tu212 cells. The role of IL-17 was determined using siRNA techniques in the LC cell line. Results. In the LC patients, cytokines were dysregulated in LC tissues compared with normal tissues. It was found that IL-17 was overexpressed in a cohort of 60 LC tumors paired with nontumor tissues. Moreover, high IL-17 expression was significantly associated with the advanced T category, the late clinical stage, differentiation, lymph node metastasis, and recurrence. In addition, the time course expression of FAS and FASL was observed after stimulation and treatment with the IL-17 stimulator. Finally, in vitro experiments demonstrated that IL-17 functioned as an oncogene by inhibiting the apoptosis of LC cells via the PI3K/AKT/FAS/FASL pathways. Conclusions. In summary, these findings demonstrated for the first time the role of IL-17 as a tumor promoter and a prometastatic factor in LC and indicated that IL-17 may have an oncogenic role and serve as a potential prognostic biomarker and therapeutic target in LC.